2020
DOI: 10.1101/2020.09.23.20199463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Effectiveness of Famotidine in Hospitalized COVID-19 Patients

Abstract: Background: Famotidine has been posited as a potential treatment for COVID-19. We compared the incidence of COVID-19 outcomes (i.e., death; and death or intensive services use) among hospitalized famotidine users vs. proton pump inhibitors (PPIs) users, hydroxychloroquine users or famotidine non-users separately. Methods: We constructed a retrospective cohort study using data from COVID-19 Premier Hospital electronic health records. Study population were COVID-19 hospitalized patients aged 18 years or older. F… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Using PHD, the authors identified 1,816 users of famotidine, 2,193 users of PPIs, 5,950 users of the hydroxychloroquine, and 26,820 nonfamotidine users. 38 Although it is substantially larger than other EHR-based studies on the same topic, 39 PHD does not contain laboratory results to confirm COVID-19 status, and the study cohort was defined as "condition, measurement or observation indicative of COVID-19." 38 In an inpatient setting, medication information can be generated at the following stages.…”
Section: Data Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…Using PHD, the authors identified 1,816 users of famotidine, 2,193 users of PPIs, 5,950 users of the hydroxychloroquine, and 26,820 nonfamotidine users. 38 Although it is substantially larger than other EHR-based studies on the same topic, 39 PHD does not contain laboratory results to confirm COVID-19 status, and the study cohort was defined as "condition, measurement or observation indicative of COVID-19." 38 In an inpatient setting, medication information can be generated at the following stages.…”
Section: Data Sourcesmentioning
confidence: 99%
“…38 Although it is substantially larger than other EHR-based studies on the same topic, 39 PHD does not contain laboratory results to confirm COVID-19 status, and the study cohort was defined as "condition, measurement or observation indicative of COVID-19." 38 In an inpatient setting, medication information can be generated at the following stages. (i) Electronic ordering data are produced when physicians prescribe a medication in the EHR system.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational Health Data Sciences and Informatics (OHDSI) is an international, multi-stakeholder collaboration that has developed open-source solutions for large-scale analytics [4]. The OHDSI community has used these open-source solutions to generate observational evidence for COVID-19 and has impacted international clinical guidelines [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%